Entre amarras e possíveis : atividade de trabalho e modos de viver dos policiais militares capixabas em análise - Magalhães, Janice do Carmo Demuner (2015)
This study, conducted between 2012 and 2014, aimed to analyze, under the bias of Ergology and Michel Foucault’s contributions, the relationship between the work activities of the military policemen of Espírito Santo and the production of certain military policeman models that are currently constituted. In this perspective, it was sought to enlace an analysis that articulates knowledge, standards and subjective productions regarding the military police activity. The strategies used during this study were grounded in the perspective of the cartographic method, whose data production occurs jointly to the workers. Thus, the methodology included: monitoring of two courses given at the Training and Improvement Center of Military Police of Espírito Santo – Soldiers Training Course and Sergeants Qualification Course –; conducting three interviews with sergeants and three interviews with soldiers; holding a focus group with ten sergeants; accompanying solemnities of PMES and reading some of the regulations that guide the Corporation. From this path, it was observed that the activity of the military policeman is marked by unpredictability and crossed by the principles of hierarchy and discipline, which will lay the foundations for the relationships within and outside the barracks. It was concluded that being a policeman requires a number of rules and conformation/organization of ways of life that will contribute to set up a certain condition of military policeman. Finally, we affirm the importance of further studies to look into the activity of the policemen, taking into account the knowledge of the workers themselves.